A tropical fish yearns for snow. 8 - Hagino, Makoto; Werry, John (Translator) (Viz Media, LLC, 2021)
"The Aquarium Club is finally coming alive after welcoming new members, but summer is nearing and Koyuki has started studying hard for exams. Working up her resolve, Koyuki invites Konatsu on a moonlit walk on the beach where she bares her heart about an important choice. Graduation is approaching and the time they have left together is more precious than ever, but how does Konatsu respond to hearing Koyuki's decision?"--Back cover.